Application of Unit-Level Cost Transparency, Education, Enhanced Audit, and Feedback of Anonymized Peer Ranking to Promote Judicious Use of 25% Albumin in Critical Care Units. (June 2020) - Udeh, Chiedozie I.; Wanek, Matthew; Udeh, Belinda L.; Hata, J. Steven
Objective: Hyperoncotic 25% albumin is widely used for fluid resuscitation in intensive care units. However, this practice remains controversial. By 2012 in our intensive care unit, annual 25% albumin expenditures had steadily increased to exceed $1 million. This prompted efforts to promote more judicious use.Design: Prospective time series cohort analysis using statistical process control charts.Setting: Seventy-six-bed quaternary level cardiovascular surgical intensive care unit (CVICU), organized into 6 adjacent units.Patients: Adult cardiac, thoracic, and vascular surgery patients admitted postoperatively to the CVICU during the study period.Interventions: Over 12 months starting March 2013, we sequentially implemented unit-level 25% albumin cost transparency, provider education, and individualized audit and feedback of anonymized peer ranking of albumin prescriptions.Measurements and Main Results: C control charts were used for analysis of monthly unit-level direct albumin costs for 20 months. Balance measures including red cell transfusions, number of diagnoses of pleural effusions, and length of stay were also tracked. Monthly average albumin expenditures had decreased 61% by December 2014, and there was no evidence of adverse changes in any of the balance measures. These reductions have been sustained.Conclusion: Sequential implementation of multimodal strategies can alter clinician practices to achieve substantial unit-level reduction in 25% albumin utilization without harm to patients.